Basic measurements of radiation at station São Marinho de Serra (2006-04 et seq) - André R Goncalves; Enio Bueno Pereira (PANGAEA, 2025)
This is a compilation of all short-wave and long-wave radiation datasets from Sao Marinho de Serra that were and are published in the frame of BSRN. New data will be added regularly. The data are subject to the data release guidelines of BSRN (https://bsrn.awi.de/data/conditions-of-data-release/).